Friends don't fall in love : a novel - Hahn, Erin (St. Martin's Griffin, 2023)
"Erin Hahn's Friends Don't Fall in Love is about long-time friends, taking chances, and finding out that, sometimes, your perfect person was right there in your corner all along. Lorelai Jones had it all: a thriving country music career and a superstar fiancé. Then she played one teenie tiny protest song at a concert and ruined her entire future, including her impending celebrity marriage. But five years later, she refuses to be done with her dreams and calls up the one person who stuck by her, her dear friend and her former fiancé's co-writer and bandmate, Craig. Craig Boseman's held a torch for Lorelai for years, but even he knows the backup bass player never gets the girl. Things are different now, though. Craig owns his own indie record label and his songwriting career is taking off. If he can confront his past and embrace his gifts, he might just be able to help Lorelai earn the comeback she deserves--and maybe win her heart in the process. But when the two reunite to rebuild her career and finally scratch that itch that's been building between them for years, Lorelai realizes a lot about what friends don't do. For one, friends don't have scratch-that-itch sex. They also don't almost-kiss on street corners, publish secret erotic poetry about each other, have counter-top sex, write songs for each other, have no-strings motorcycle sex, or go on dates. And they sure as heck don't fall in love... right?"--